Production and Comprehension of Prosodic Markers in Sign Language Imperatives - Brentari, Diane; Falk, Joshua; Giannakidou, Anastasia; Herrmann, Annika; Volk, Elisabeth; Steinbach, Markus (Frontiers in Psychology, 2018)
In signed and spoken language sentences, mood and their corresponding imperative speech acts can be distinguished by morphosyntactic cues, but also solely by prosodic cues, which are the focus of this paper. These cues lie between those expressing mental states and those expressing grammatical meaning. The production and comprehension of prosodic facial expressions and temporal patterns therefore can shed light on how prosodic cues are grammaticalized in sign languages. They can also be informative about the formal semantic and pragmatic properties of imperative types not only in American Sign Language (ASL), but also more broadly. This paper includes three studies: one of production (Study 1) and two of comprehension (Studies 2 and 3). In Study 1, six prosodic cues were analyzed: temporal cues of sign duration and hold and non-manual cues including tilts of the head, head nods, widening of the eyes, and presence of mouthing. Results of Study 1 show that neutral sentences and commands were well distinguished from each other and from other imperative speech acts via these six prosodic cues alone; there was more limited differentiation among explanation, permission, and advice. The comprehension of these five speech acts were investigated in Deaf ASL signers in Study 2, and in three additional groups in Study 3: Deaf signers of German Sign Language (DGS), hearing non-signers from the United States, and hearing non-signers from Germany. Results of Studies 2-3 show that the ASL group performed significantly better than the other 3 groups, and that all groups perform above chance for all meaning types in comprehension. Language-specific knowledge, therefore, has a significant effect on identifying imperatives based on prosodic cues. Command has the most cues associated with it and is the most accurately identified imperative type across groups. Our findings support the view that these cues are accessible in their content across groups, but that their language-particular combinatorial possibilities and distribution within sentences provide an advantage to ASL signers in comprehension.